An effective load shedding remedial action scheme considering wind farms generation. (February 2018) - Atighechi, Hamid; Hu, Po; Ebrahimi, Seyyedmilad; Lu, Jun; Wang, Guihua; Wang, Liwei
Highlights: Developing a fast load shedding remedial action scheme considering local generations. The dynamics of wind farms are included in the shedding requirements and formulas. The shedding candidates are selected and prioritized. The effectiveness of the proposed methodology is verified using PSSE simulation. Using the proposed approach, load shedding requirements can be considerably reduced. Abstract: In this paper, a fast load shedding remedial action scheme (RAS) is developed considering generation pattern of local wind farms using wide area monitoring framework. In the proposed RAS, the shedding candidates are selected and prioritized based on load types and their impacts on the voltage profile and transient performance of the system. The dynamics of wind farms are also included in the shedding requirements and formulas by defining effectiveness indices which are calculated based on the contribution of each generator to the dynamic performance of the system. This allows secure operation of the system after major contingencies while impacted customers are minimized. The proposed methodology, shedding formulas, and corresponding requirements are verified for the BC Hydro system using the PSS/E dynamic simulation package.